Location related determinants of foreign direct investment in Yemen: Dunning's eclectic paradigm perspective - Almsafir M.K.; Nor S.M.; Al-Shibami A.H. (2023)
This paper particularly is concerned with determining and estimating factors influencing Foreign Direct Investment (FDI) in Yemen. The paper is based on the location related perspective, Dunning's Eclectic Paradigm Model. The paper aims to explore the determinants of the inflows and performance of FDI in Yemen by using primary data, reports on an empirical study based on 70 companies that have conducted FDI in Yemen. The simple and multiple regression models are used for data analysis and test hypotheses for this study. The Statistical Package for Social Science (SPSS) version 18.0 was employed to achieve the study's objective. Yemen, like most of other developing countries, has made substantial changes in all aspects related to the attraction of FDI. In that respect, we performed whether the institutions and managerial rules, investment incentives, and geographical location and economic agglomeration have influenced the inflows and the performance of FDI in Yemen. However, Yemen among other countries in West Asia region still suffers from relatively abysmal and disappointing record of FDI. It is found that from the location related factors perspective, Yemen hasn't reached the point to be an attractive location for FDI.